2012
DOI: 10.1111/j.1745-4549.2012.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postharvest Putrescine Application and Chitosan Coating on Maintaining Quality of Table Grape Cv. “Shahroudi” During Long-Term Storage

Abstract: The role of postharvest application of putrescine (PUT) alone or in combination with chitosan (CH) on maintaining quality of fresh table grapes (Vitis vinifera) cultivar “Shahroudi” was investigated. The clusters were dipped in an aqueous solution containing different concentrations of PUT (0, 1 and 2 mM). Following PUT treatments, some fruits were coated with 1% w/v CH. After treatment, fruits were stored at 0 ± 1C and 90 ± 5% relative humidity for 60 days and 5 additional days in evaluation room. The general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…Similarly, the combination of chitosan with potassium metabisulfite was tested in litchi fruit. Both chitosan and the combination of chitosan and potassium metabisulfite decreased postharvest decay of these litchi fruit (Sivakumar et al, 2005a).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Similarly, the combination of chitosan with potassium metabisulfite was tested in litchi fruit. Both chitosan and the combination of chitosan and potassium metabisulfite decreased postharvest decay of these litchi fruit (Sivakumar et al, 2005a).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, if harvested at the correct maturity and packed (selected bunches which are free from any visible damages) in ventilated CFB boxes of 4 kg capacity, lined with LDPE containing one sheet of grape guard and stored at low temperature (0 -2 o C, 90 -95 % RH), the grapes can be kept for up to 45 -50 days with acceptable market quality (Mahajan et al, 2011), which can gain premium prices at the end of the season. Shiri et al (2012) have reported that a combination of 1 mM putrescine (a diamine) dip treatment followed by coating with 1 % chitosan reduced the rate of weight loss, decay incidence, rachis browning and berry shattering in grape cv. Shahroudi stored at 0 ± 1 o C, 90 -95 % RH for up to 60 days.…”
Section: Storagementioning
confidence: 99%
“…The relatively higher content of phenolic in ultrasound treated alone and combined with Put was observed. Similarly, previous studies showed that Put treatments had significant positive effect on phenolic compound of fruits (Shiri et al, 2012;Davarynejad et al, 2013). At the end of the storage, the highest total phenolic content was found in Put 2+ultrasound treatment (340.9 mg*100 g .…”
Section: Total Phenolic Contentmentioning
confidence: 80%
“…Flame Seedless for up to 60 days in cold storage. Further, postharvest Put-treated berries (1 and 2 mM) exhibited higher total phenolic content, catechin, total quercetin and antioxidant activity (Shiri et al, 2012).…”
Section: Introductionmentioning
confidence: 99%